Polish Avant-Garde in Berlin - Stolarska-Fronia, Małgorzata (Peter Lang International Academic Publishing Group, 2019)
This book presents a historical panorama of the Polish avant-garde in Berlin from 19th century historical avant-garde until the recent art. Looking at specific artistic strategies and development of modernist paradigm both in the pre- and post-Second World War period from the perspective of the migration experience, this book offers a deep insight into mechanisms, relations and identity programmes of particular artists or groups. It also reveals the dynamics of eventual cultural exchange or alternative forms of artistic transformation and message that Polish artists imprinted in the Berlin's art scene. Whether historical avant-garde or the neo-avant-garde, the component of novelty inscribed in the term itself ceases to be a sheer, one-dimensional slogan and reveals a whole range of cultural projections that artist-migrants are both creators and the subject of. Here the notion of exoticism, wilderness, but also critical and ironical approach often constitute the perception of Polish art in the Berlin milieu.